1993
DOI: 10.3758/bf03337331
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dissonance: Physiological arousal in the performance expectancy paradigm

Abstract: The physiological correlates of dissonance were investigated using a replication of Aronson and Carlsmith's (1962) performance expectancy paradigm. Dissonance was predicted to be associated with an increased heart rate and skin conductance response (SCR). This prediction was partially supported; dissonance was significantly related to heart rate changes, but not to SCR. The results are discussed in terms of their implications for the performance expectancy paradigm and its relationship to dissonance and arousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Instead, physiological measures seem to more accurately assess these responses. Measures such as heart rate variability, blood pressure, skin conductance, and neuroendocrine responses such as cortisol secretion may be more effectively used to assess threat arousal (e.g., Blascovich et al, 2001;Etgen & Rosen, 1993;Harmon-Jones, Brehm, Greenberg, Simon, & Nelson, 1996;Losch & Cacioppo, 1990;Mendes, Blascovich, Lickel, & Hunter, 2002;Townsend, Major, Gangi, & Mendes, 2011).…”
Section: Physiological Stress Responsementioning
confidence: 99%
“…Instead, physiological measures seem to more accurately assess these responses. Measures such as heart rate variability, blood pressure, skin conductance, and neuroendocrine responses such as cortisol secretion may be more effectively used to assess threat arousal (e.g., Blascovich et al, 2001;Etgen & Rosen, 1993;Harmon-Jones, Brehm, Greenberg, Simon, & Nelson, 1996;Losch & Cacioppo, 1990;Mendes, Blascovich, Lickel, & Hunter, 2002;Townsend, Major, Gangi, & Mendes, 2011).…”
Section: Physiological Stress Responsementioning
confidence: 99%
“…Given the amount of evidence, it seems indisputable that cognitive dissonance is associated with elevated arousal. However, some deviations across these results should be noted: contrary to the results in the freechoice paradigm, studies involving writing counterattitudinal essays have not found an elevation in heart rate (Croyle & Cooper, 1983); similarly, contrary to the results for the counterattitudinal essay paradigm, studies utilizing unexpected feedback have not found an elevation in GSR (Etgen & Rosen, 1993). These discrepancies are also noticeable in neuronal studies.…”
mentioning
confidence: 59%
“…For instance, writing a counterattitudinal essay is the predominant task used to generate an inconsistency between an attitude and a behaviour, and studies found elevated galvanic skin responses (GSR) during and after the writing of such essays (Croyle & Cooper, 1983;Elkin & Leippe, 1986;Harmon-Jones, Brehm, Greenberg, Simon & Nelson, 1996;Losch & Cacioppo, 1990). The free-choice paradigm and receiving feedback contrary to expectations are two other paradigms that have been associated with elevated heart rate (Etgen & Rosen, 1993;Gerard, 1967;Mann, Janis & Chaplin, 1969). Examinations of neuronal activity have shown a lower level of alpha waves when doing an unpleasant task without enough justification (McMillen & Geiselman, 1974) as well as the involvement of specific brain areas such as the anterior cingulate cortex during cognitive dissonance studies involving counterattitudinal tasks or the free-choice paradigm (for review, see Izuma & Murayama, 2019).…”
mentioning
confidence: 99%
“…It is conceivable that respondents may have avoided cognitive dissonance (Etgen and Rosen, 1993;Festinger and Aronson, 1997), meaning that it is not very likely they will rate a course as effective while at the same time rating the strategic aligning process as poor. Multilevel statistical models are used to handle this problem.…”
Section: The Problem Of Cognitive Dissonancementioning
confidence: 99%